Memory and migration : multidisciplinary approaches to memory studies - Creet, Julia, 1958-; Kitzmann, Andreas (University of Toronto Press, 2011)
Memory plays an integral part in how individuals and societies construct their identity. While memory is usually considered in the context of a stable, unchanging environment, this collection of essays explores the effects of immigration, forced expulsions, exile, banishment, and war on individual and collective memory. The ways in which memory affects cultural representation and historical understanding across generations is examined through case studies and theoretical approaches that underscore its mutability. Memory and Migration is a truly interdisciplinary book featuring the work of leading scholars from a variety of fields across the globe. The essays are collaborative, successfully responding to the central theme and expanding upon the findings of individual authors. A groundbreaking contribution to an emerging field of study, Memory and Migration provides valuable insight into the connections between memory, place, and displacement.--